2014
DOI: 10.1177/0145721714540220
|View full text |Cite
|
Sign up to set email alerts
|

Update on Health Literacy and Diabetes

Abstract: Purpose Inadequate literacy is common among patients with diabetes and may lead to adverse outcomes. We reviewed the relationship between literacy and health outcomes in patients with diabetes and potential interventions to improve such outcomes. Methods We reviewed 79 articles covering three key domains: 1) evaluation of screening tools to identify inadequate literacy and numeracy; 2) the relationships of a range of diabetes-related health outcomes with literacy and numeracy; and 3) interventions to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
241
1
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(292 citation statements)
references
References 78 publications
14
241
1
15
Order By: Relevance
“…Our research study is consistent with other studies that demonstrate that pharmaceutical care intervention can improve disease-related knowledge, clinical markers, and medication adherence in patients with hypertension and/or diabetes [15][16][17]. Future research with a larger sample size and a longer duration of time may determine if the effect of pharmacist management on disease-related knowledge, haemoglobin A1C, blood pressure and medication adherence is sustainable after study completion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our research study is consistent with other studies that demonstrate that pharmaceutical care intervention can improve disease-related knowledge, clinical markers, and medication adherence in patients with hypertension and/or diabetes [15][16][17]. Future research with a larger sample size and a longer duration of time may determine if the effect of pharmacist management on disease-related knowledge, haemoglobin A1C, blood pressure and medication adherence is sustainable after study completion.…”
Section: Discussionsupporting
confidence: 89%
“…There are 36 items that are administered in 7 minutes. The scoring categorizes respondents into inadequate (0-16), marginal (17)(18)(19)(20)(21)(22) or adequate levels (23-36) of health literacy [12].…”
Section: Methodsmentioning
confidence: 99%
“…A literacia em saĂșde, ou as "competĂȘncias cognitivas e sociais e a capacidade dos indivĂ­duos para ganharem acesso a compreenderem e a usarem informação de formas que promovam e mantenham boa saĂșde" 31 Ă© um possĂ­vel mecanismo explicativo da relação entre o nĂ­vel educacional e as desigualdades em saĂșde. Revelou estar associada em vĂĄrios estudos com menores conhecimentos sobre a diabetes, 32 baixa adesĂŁo nĂŁo intencional Ă  terapĂȘutica na diabetes 33 e constituir uma barreira na acessibilidade aos serviços e informação de saĂșde e aos meios de prevenção. 34 O rendimento tambĂ©m se associou Ă  desigualdade observada mas com menor efeito.…”
Section: Discussionunclassified
“…Results: Diabetes was found to be concentrated among the people with lower educational levels (concentration index = -0.26) and lower income quintiles (concentration index = -0.14). Relative index of inequality also showed a lower degree of inequality among the most educated (0,20; CI 95% = [0,12; 0,32]) and with higher income (0,59; CI 95% = [0,48; 0,74]). Discussion: Distribution of diabetes is associated with education and income.…”
mentioning
confidence: 94%
“…A recent paper has identified that health literacy is still only marginally addressed in different aspects of work [46]. Low literacy is related to poor knowledge and may impact on health outcomes [47,48]. A study of 280 adults with poor glycaemic control showed that those with low health literacy perceived that their diabetes control was good when it was not [49].…”
Section: Health Literacymentioning
confidence: 99%